An Argument for the U.S. Higher Education Bubble - Kasanová, Barbora (2016)
Unsustainable business practices coupled with an illusion of the masses plagues the higher education model in the United States today. It used to hold that college was the key to a successful job for fresh graduates. . . . We are in the midst of a speculative bubble composed of inflated expectations about the university system. This paper aims to analyze that there is indeed a speculative bubble of the US Higher Education system. The increased demand for college, skyrocketing tuition and room & board fees, as well as easier access to loans for funding have contributed to the formation of this bubble.